Spontaneous rupture of the renal pelvis caused by upper urinary tract obstruction: A case report and review of the literature. Issue 50 (December 2017) - Zhang, Huaming; Zhuang, Guimin; Sun, Dongchong; Deng, Tianxing; Zhang, Jiawei
Abstract: Rationale: Spontaneous renal rupture is rupture of the renal parenchyma, collecting system, or renal blood vessel, which often occurs in pathological kidney and is clinically less common. Postoperative long-term renal rupture is rarely reported in flexible ureteroscopy treatment of calculus in the upper urinary tract. Patient concerns: A 58-year-old man complained of right lower abdominal pain with hematuria for 3 hours after flexible ureteroscopy, combined with holmium laser lithotripsy of right renal calculi was performed 1 month ago. The urinary B-mode ultrasonogram suggested calculi and dilatation at the end of the right ureter, and moderate hydronephrosis of the right kidney. On the second day, the urinary system computed tomography (CT) examination suggested right renal rupture. Diagnosis: Spontaneous rupture of the right renal pelvis. Intervention: The patient underwent conservative treatment after the optimal treatment strategy was reviewed and discussed. Outcomes: Urinary system CT re-examination suggested complete absorption of the hematoma and urinary extravasation 3 months later. Lessons: Calculi obstruction is the most important cause of spontaneous renal rupture. CT is a valuable diagnostic modality, and spontaneous renal rupture should receive tailored treatment.